The Role of Strategic Marketing in Organizations immersed in VUCA environments - Ramírez-Torres, Margarita; Salinas-Chaidez, Erick P.; Miranda-Navarro, Ana B. (EFIM Ediciones, 2021)
Aspects such as the change in customer consumption, the increase in the number of customers and new technologies are causing an environment where volatility, uncertainty, complexity and ambiguity are common for organizations. Within this framework, an analysis of the strategic marketing management of organizations is proposed, emphasizing the importance of strategy for the management of companies, as well as the importance of measuring organizational performance and its efficiency. For such purposes, an analysis of the literature is proposed, framing the main aspects that link these topics. The results show that strategic marketing has a positive influence on the company's results, which translates into an efficient, effective and solid operation, in addition to being profitable in the long term. A good strategic plan is fundamental for the achievement of the company's business objectives and its permanence in the market